The interaction between maternal and post‐hatch n‐3 fatty acid supplementation in broiler diets. Issue 5 (9th March 2015) - Koppenol, A.; Delezie, E.; Buyse, J.; Everaert, N.
Summary: This study investigated whether offspring from n‐3‐supplemented breeders have an enhanced performance and immune organ weight when fed a post‐hatch n‐3‐enriched diet in comparison with their control‐fed counterparts and the importance of timing of omega‐3 supplementation. Therefore, 480 Ross‐308 broiler breeder hens were fed one of four different diets (120/treatment). The control diet (CON) was a basal diet, rich in n‐6 fatty acids (FA). The three other diets were enriched in n‐3 FA, formulated to obtain a different EPA/DHA ratio of 1/1 (EPA = DHA), 1/2 (DHA) or 2/1 (EPA). At 33 weeks of age, eggs were incubated to obtain 1440 offspring. They were set up according to their maternal diet and sex in 48 pens of 30 chicks each (12 pens per maternal treatment: six male and six female). Half of the offspring were given a post‐hatch control diet, whereas to other half received an n‐3‐supplemented diet. Zootechnical performance was followed for starter, grower and finisher phase, and at the end of each phase two, chicks per pen were sacrificed to determine the weight of the immune organs. No interaction was found between maternal and post‐hatch n‐3 treatment for zootechnical performance. An interaction arose between the maternal and post‐hatch n‐3 supplementation for proportional bursa weight at day 1 and day 14 and proportional liver weight at day 14, but effects on immune organ weight were rather limited. Offspring post‐hatch n‐3 supplementation did not enhance maternal n‐3 supplementation.